The hard sell of paradise : Hawai'i, Hollywood, tourism - Sperb, Jason, 1978- (Albany : State University of New York Press, 2022)
"Traces the complex and contradictory representations of Hawai'i in popular film and television programs from the 1930s to the 1970s"--
Introduction: touristic visions and virtual tourists -- 1. Save that gag for the tourists: the Hawaii Tourists Breau and post-tourism narratives of 1930s Hollywood -- 2. Twilight of the past, island of utopia: December 7th and the contradictions of war nostalgia -- 3. Your're still talking about class? adapting statehood Diamond Head (1963) -- 4. Founded on truth but not fact: pastiche narratives of modernity in adaptions of James Michener's Hawaii (1959) -- 5. Business or pleasure: the touristic contradictions of the Elvis/Hawai'i experience from Blue Hawaii (1961) to Aloha from Hawaii (1973) -- 6. Shoot all winter, show all summer: frontier mythologies and the hipster tourism of surf documentaries -- 7. If you can't find it, don't write it: genre and competing notions of realism in Hawaii Five-O (1968) -- Conclusion: Hawai'i bound.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on March 25, 2022).
JSTOR
Keywords: Hawaii -- On television; Motion pictures -- United States -- History -- 20th century; Television programs -- United States -- History -- 20th century; Hawaii -- In motion pictures; Hawaii -- In popular culture; Cinéma -- États-Unis -- Histoire -- 20e siècle.; Émissions télévisées -- États-Unis -- Histoire -- 20e siècle.; Hawaii -- Dans la culture populaire; Hawaii -- À la télévision.; PERFORMING ARTS / Film & Video / History & Criticism; Motion pictures; Television programs; Hawaii; United States; 1900-1999; History